Implementasi Algoritma Jean Meeus dalam Penentuan Gerhana Bulan dan Matahari - Andini, Baiq Anggi; Adawiyah, Siti Rabi'atul; Sado, Arino Bemi (Universitas Islam Negeri Mataram, 2023)
This study aims to determine the implementation and accuracy of the Jean Meeus Algorithm in determining lunar and solar eclipses.This research is a qualitative research with a literature approach. The primary data source for this research is a book entitled Astronomical Algorithm by Jean Meeus. Meanwhile, secondary data is all information related to the Jean Meeus algorithm in determining eclipses obtained from various literature such as books, websites, encyclopedias, dictionaries, scientific articles, and other sources of information. The results of this study indicate that determining the eclipse time using the Jean Meeus algorithm involves seven stages of calculation namely; starting with determining the year the eclipse occurred, then determining the gamma value, JDE (Julian Day Ephemeris), the payoff value (k), the saros series, the reference time (To) and the Bessel Element value. The calculation of the Jean Meeus Algorithm is included in the tahkiki essential reckoning method because the calculation process involves astronomical data with very precise corrections for the motion of the Moon and the Sun, This method is also based on the heliocentric flow. In addition, the level of accuracy of Jean Meeus' calculations has a good match with NASA as a comparison, namely with results that are only 1 to 3 minutes apart and the average difference is only in seconds.